If f(x)=3x^2+1 and g(x)=1-x, what is the value of (f-g)(2)?
2 answers:
The answer is 14 you just have to substitute x with the given number and finish the equation
Answer:
(f – g)(2) = 12.
Step-by-step explanation:
Given : f(x) = 3x²+1 and g(x) =1-x .
To find : which expression is equivalent to (f – g)(2).
Solution : We have given f(x) = 3x²+1 and g(x) = 1-x .
(f – g)(2) = f (2 ) - g(2) .
g(x) = 1-x .
Plug x = 2 .
g(2) = 1 - 2 .
g(2) = - 1.
For f(x) =3x²+1
Plug x = 2
f( 2) =3 (2)²+1.
f(2) = 12 + 1.
f(2) = 13 .
Then , (f – g)(2) = f (2 ) - g(2) .
Plugging the values
(f – g)(2) = -1 + 13
(f – g)(2) = 12
(f – g)(2) = 12.
Therefore, (f – g)(2) = 12.
You might be interested in
Answer:
6.74
Step-by-step explanation:
may be it is .......
Answer:
it is a function
Step-by-step explanation:
the input is not repeated
Answer:
B. 3√2.
Step-by-step explanation:
-3√2 + 3√4x2 -3√2 + 6√2 3√2 These are all of the steps to completely, find the correct answer to your question.
Hope this helps!!!
Kyle.
The ratio birds : animals = 13 : 2 so for every 1 animal, 6.5 birds were born last month: animals = birds - 44 birds - animals = 44 use trial and improvement to find: if there were 52 birds, there must be 8 animals CHECK: 52 - 8 = 44
Answer:
Step-by-step explanation:
360